Pengaruh Terpaan Berita Satwa Laut yang Mati Akibat Sampah Plastik dan Kampanye Zero Waste terhadap Perilaku Pengurangan Penggunaan Kantong Plastik - Randyani Rarasati; Tandiyo Pradekso (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2019)
This study aims to determine the effect of news exposure about marine animals that killed by plastic pollution and zero waste campaigns toward the behavior of reducing the use of plastic bags. The theory used in this research is the effect of mass communication theory and Cognitive response theory. To determine the sample, this study uses a non-probability sampling technique by accidental sampling. The number of samples studied amounted to 60 people with the characteristics of men/women domiciled in the city of Semarang, aged 19-34 years, had heard and/or read news of marine animals killed by plastic pollution and had heard/known of the zero waste campaign. The results showed that the exposure of marine animals that killed by plastic pollutions to the behavior of reducing the use of plastic bags had no significance value, it showed that the hypothesis and the theory are rejected. Furthermore, the effect of zero waste campaign exposure on the behavior of reducing the use of plastic bags showed a significant influence with the positive regression, which means that the increase of zero waste campaign exposure directly proportional to the behavior of reducing the use of plastic bags.